The Influence of the Headmaster’s Managerial Functions on the Formation of Religious Character at MI Al Marzukiah, Central Lombok (PT. LARPA JAYA PUBLISHER, 2024)
This study aims to examine the personality competence of the Madrasah Principal and its influence on the character development of students at MI Al Marzukiah, Central Lombok. The research employed a descriptive and inferential quantitative approach with a total of 46 respondents, including teachers and students. Descriptive analysis revealed that the principal’s personality competence predominantly falls into the moderate category (65%), while student character development is also mostly moderate (76%). The personality competence of the principal encompasses the ability to lead, motivate, and coordinate the madrasah community, including teachers, staff, and students, in achieving educational goals, as regulated by the Ministry of Religious Affairs No. 58 of 2017 and the Ministry of National Education No. 13 of 2017. Inferential statistical analysis using the t-test showed no significant effect of the principal’s personality competence on student character development (tcount = 0.601 < ttable = 1.680, ? = 0.05). This suggests that student character development is influenced more by teachers’ daily interactions, school environment, parental involvement, and students’ own initiative rather than solely by the principal’s personality. The findings emphasize the importance of a collaborative approach in character education, integrating school leadership, teacher facilitation, family support, and environmental factors to cultivate dynamic and value-based character aligned with Islamic principles.